2016
DOI: 10.15666/aeer/1405_137147
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Salt Stress by K2so4 in Two Wheat (Triticum Aestivum L.) Cultivars

Abstract: Abstract. Salinity is a major abiotic stress which adversely affects productivity of all crops in the world specifically in cereals. Different strategies are being utilized to enhance the overall plant growth and productivity all over the world. The crop nutrients management is one the best options to increase the plant productivity in saline soils. The present study investigated the influence of potassium sulphate (K 2 SO 4 ) in improving plant productivity and nutrient uptake in wheat grown under saline envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Control treatment T 0 (K 0 Zn 0 ) produced the lowest straw yield (4.91 t/ha) which was identical with T 1 (K 0 Zn 100 ) treatment (Figure 1). In agreement with our results, Kausar et al (2016); Kamrani et al (2013); Heidari and Jamshid (2010) found that grain and straw yields of wheat increased due to application of potassium and zinc fertilizers at higher doses in salt-stress conditions.…”
Section: Straw Yieldsupporting
confidence: 93%
“…Control treatment T 0 (K 0 Zn 0 ) produced the lowest straw yield (4.91 t/ha) which was identical with T 1 (K 0 Zn 100 ) treatment (Figure 1). In agreement with our results, Kausar et al (2016); Kamrani et al (2013); Heidari and Jamshid (2010) found that grain and straw yields of wheat increased due to application of potassium and zinc fertilizers at higher doses in salt-stress conditions.…”
Section: Straw Yieldsupporting
confidence: 93%
“…Salinity is a common environmental condition that inhibits plant growth and development, resulting in reduced agricultural productivity (1,2). Salinity induced desertification occurs in arid and semi-arid areas across the world when agricultural land is lost over time (3).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results are consistent with the most previous investigations, which pointed out the same direct correlation between antitranspirant materials and some element nutrient to tissues of soya bean (Yadav and Dashora 2003). Kausar et al (2016) reported that the nutrient uptake and accumulation such as Ca, Mg, K, and P were gradually increased by K application particularly under saline environments in both wheat genotypes. Abd El-Samad et al (2018) found that the potassium application that increased significantly gained the highest percentage values of total soluble solids (TSS), protein, N, P, and K of bean plants.…”
Section: Mineral Nutrients Of the Grain Yieldmentioning
confidence: 95%